2010
DOI: 10.1080/07347332.2010.488146
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation of Cancer Survivorship Experiences Among Rural Hispanics

Abstract: Cancer survivorship experiences were explored among Hispanic men and women with cancer and family members of cancer survivors, recruited from two rural Washington communities in the Lower Yakima Valley. Five focus groups were conducted from February 2006-October 2007 with 31 women and 10 men. Disbelief, fear, sadness, strength, courage, faith, and hope were common reactions to diagnosis. Concerns about family/children, losing medical coupons, and feelings of depression/isolation were identified as challenges f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…This belief is defined as the inability to affect fate or prevent cancer and is often associated with a moral framework that cancer is a punishment from God. Additional culturally based factors include embarrassment, confusion about the role of preventive medicine, and limited proficiency of the English language (Austin, Ahmand, McNally, & Stewart, 2002;Livaudais et al, 2010). These culturally based factors may contribute to the higher incidence of late stage diagnosing and increased mortality rates among Hispanic women who have been diagnosed with breast cancer (Watlington, Byers, Mouchawar, Sauaia, & Ellis, 2007).…”
Section: Living Inmentioning
confidence: 96%
“…This belief is defined as the inability to affect fate or prevent cancer and is often associated with a moral framework that cancer is a punishment from God. Additional culturally based factors include embarrassment, confusion about the role of preventive medicine, and limited proficiency of the English language (Austin, Ahmand, McNally, & Stewart, 2002;Livaudais et al, 2010). These culturally based factors may contribute to the higher incidence of late stage diagnosing and increased mortality rates among Hispanic women who have been diagnosed with breast cancer (Watlington, Byers, Mouchawar, Sauaia, & Ellis, 2007).…”
Section: Living Inmentioning
confidence: 96%
“…Codes were used to discern broad themes and patterns. Many of the themes that emerged in this study were previously identified in a robust study conducted, independently, in a similar target population and geographic region[16] offering an opportunity for replication and showing saturation had been reached for those themes. Therefore, although described below, percentages or frequencies are not reported for these themes[35, 36].…”
Section: Methodsmentioning
confidence: 76%
“…Although, for some topics (e.g., body image, exercise, spirituality and social support) the frequency of selection differed between men and women, the fact some of these topics were discussed during the qualitative assessment and there were some men who demonstrated an interest in these topics, the research team determined that topics meeting the above inclusion criteria should be incorporated into the program in an effort to evaluate the acceptability of the topics to both men and women, as well as, the potential willingness of each gender to discuss the topics that had previously been identified by both Latino men and women (from the same geographic region) as important to cancer survivorship[16]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations